Pterygium – lying in wait menace - Robaszkiewicz, Jacek; Mrzygłód, Stanisław (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
Pterygium consists of epithelium of bulbar conjunctiva and hypertrophied subconjunctival connective tissue. Although described and recognized before 1000 B. C, its pathogenesis still remains an ophthalmic enigma. Generally it is considered to be a cause of corneal blindness. The methods of pterygium surgery changes from the simplest bare sclera excision to stratified keratoplastics and transplantation technique.